Ideal and actual intervals to first birth in Singapore. Issue 1 (2nd January 2022) - Tan, Poh Lin
ABSTRACT: Postponement of first births is a key cause of declining fertility rates, especially in East Asia where recovery from delayed childbearing has been weak. This paper investigates achievement of ideal ages at marriage and first birth in Singapore using survey data on 657 married women aged 25–34. Almost 50 per cent marry within one year of their ideal age, but less than 30 per cent have their first child within six months of their ideal interval to first birth, with around 50 per cent waiting longer than ideal. The high proportion of women experiencing a longer-than-ideal first birth interval was observed across all age and educational groups. Regression results show that co-residence with a foreign domestic worker and paid leave entitlements are associated with higher probability of achieving their ideal first birth interval, whereas availability of parents/in-laws, husband's help and unpaid leave do not reduce time to childbearing.